JIHAD DALAM PANDANGAN MUHAMMAD SHAHRUR - Nur Mahmudah (Jurnal Theologia, 2012)
The acts of violence and terrorism committed by a group of Muslims is not based on a complete understanding of some important concepts in the Koran as the concept of jihad. This concept is often identified with the support of acts of terrorism and violence in the name of Islam-sanctioned religion. Until now, this view can still be found in some Muslim groups so some efforts to reconceptualize this view are badly needed. The focus of this paper is an attempt of Muhammad Shahrur in reviewing this concept with an approach of inter-textuality that utilizes syntagmatic-paradigmatic analysis to embed chaff theological views of war and campaigning peace Jihad in Islam. Tindakan kekerasan dan terorisme yang dilakukan oleh sekelompok umat Islam didasarkan pada pemahaman yang tidak paripurna terhadap beberapa konsep penting dalam al-Quran seperti konsep jihad. Konsep ini sering diidentikkan dengan dukungan tindakan terorisme dan kekerasan atas nama agama yang direstui Islam. Hingga kini pandangan ini masih dapat ditemukan dalam beberapa kelompok muslim sehingga diperlukan upaya rekonsepsi terhadapnya. Fokus tulisan ini adalah upaya Muhammad Shahrur mengkaji ulang konsep ini dengan pendekatan intertekstualitas yang memanfaatkan analisis sintagmatik-paradigmatik untuk  memadamkan sekam pandangan teologi perang dan mengkampayekan jihad damai dalam Islam